2010
DOI: 10.1159/000273207
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Weekly Nedaplatin, External Beam Radiotherapy and High-Dose-Rate Brachytherapy in Patients with FIGO Stage IIIb Cervical Cancer: A Comparison with a Cohort Treated by Radiotherapy Alone

Abstract: Objectives: The aim of this study was to evaluate whether nedaplatin-based concurrent chemoradiotherapy (CCRT) using high-dose-rate intracavitary brachytherapy (HDR-ICBT) is superior to radiotherapy (RT) alone in patients with FIGO stage IIIb cervical cancer. Methods: The records of 41 consecutive women treated either with nedaplatin-based CCRT using HDR-ICBT (n = 20) or RT alone (nonrandomized control group, n = 21) for stage IIIb cervical cancer were retrospectively reviewed. The activity and toxicity were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…In reference to the radiotherapy and hyperthermia modality, the complete response rate for advanced cervix cancer was 77% (Franckena et al, 2009). Additionally, treatment failure in stage IIIB cervical cancer from the study of Mabuchi et al was between 35-66.7% (Mabuchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In reference to the radiotherapy and hyperthermia modality, the complete response rate for advanced cervix cancer was 77% (Franckena et al, 2009). Additionally, treatment failure in stage IIIB cervical cancer from the study of Mabuchi et al was between 35-66.7% (Mabuchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Combinational therapy of HDRICB and EBRT has been widely used for the treatment of cervical carcinoma (Kapp et al, 1997;Mabuchi et al, 2010;Niibe et al, 2010). However, complications, including radiation proctitis and radiation cystitis, commonly occur following irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose-rate intracavitary brachy therapy (HDRICB) combined with external beam radiotherapy (EBRT) showed various advantages for the management of cervical carcinoma, including elimination of personnel exposure and short treatment time with the possibility of maintaining exact applicator geometry. Therefore, this therapy combination is widely applied in Japan and parts of Europe (Kapp et al, 1997;Mabuchi et al, 2010;Niibe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nedaplatin (cis-diammine-glycoplatinum) is a derivative of cisplatin developed in Japan. Different small series have demonstrated that this agent appears to have similar effi cacy with lower renal and gastrointestinal toxicities compared to cisplatin [ 40 ]. Performance of non-inferiority randomized trial with nedaplatin could help identify less toxic chemoradiation regimens.…”
Section: Combining Chemoradiation and Adjuvant Chemotherapymentioning
confidence: 99%